Pembelajaran Kooperatif Tipe CORE (Connecting – Organizing – Reflecting – Extending) Terhadap Kemampuan Komunikasi Matematis Siswa pada Siswa Kelas VIII SMP - Nina Niarti; Syahrul Azmi; Muhammad Turmuzi; Laila Hayati (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to determine the influence of the cooperative learning model CORE type on the mathematical communication skills at the eight grade students of SMPN 2 Kediri in Academic Year 2019/2020 on cube and block material. The method used in this study was a quasi-experimental research design with post-test only control group design. The population of this study were all eight grade students of SMPN 2 Kediri in academic year 2019/2020, which were distributed in three classes. The sample class was selected using cluster random sampling technique, obtained class VIII-B as the experimental class and class VIII-C as the control class. As for data collection techniques, namely observation and tests. The data analysis technique used the prerequisite test, namely the normality test and the homogeneity test followed by the pooled variance t-test. Based on the results of data analysis, it was found that there was a difference between the mathematical communication skills of students who obtained the cooperative learning model CORE type and those who used the direct learning model. Classes that using the CORE model get an average score of 77.86 while those taught with the direct learning model get an average score of 65.15. This shows that learning using the cooperative model type CORE has an influence on the mathematical communication skills of students of class VIII SMPN 2 Kediri in academic year.